Democracy as death the moral order of anti-liberal politics in South Africa - Hickel, Jason 1982- (Univ. of California Press, 2015)
"The revolution that brought the African National Congress (ANC) to power in South Africa was fractured by internal conflict. Migrant workers from rural Zululand rejected many of the egalitarian values and policies fundamental to the ANC's liberal democratic platform and organized themselves in an attempt to sabotage the movement. This antidemocracy stance, which persists today as a direct critique of 'freedom' in neoliberal South Africa, hinges on an idealized vision of the rural home and a hierarchical social order crafted in part by the technologies of colonial governance over the past century. Drawing on this ethnographic context, this work addresses the broader concerns in the literature of liberalism, democratization, and violence in the era of globalization, examining Western ideals about 'freedom' and 'agency' from the perspective of 'others.' Democracy as Death also interrogates the concept of 'interest' underpinning theories of antiliberal movements and argues that both democracy and the political science that attempts to explain resistance to it presuppose a model of personhood native to Western capitalism, which may not operate cross-culturally"--Provided by publisher